Nanostructured monoclinic Cu2Se as a near-room-temperature thermoelectric material. Issue 39 (7th October 2020) - Chen, Jie; Liu, Taoyi; Bao, Deyu; Zhang, Bin; Han, Guang; Liu, Can; Tang, Jun; Zhou, Dali; Yang, Lei; Chen, Zhi-Gang
Abstract : Nanostructured monoclinic Cu2 Se with low thermal conductivity shows a figure of merit of 0.72 at 380 K. Abstract : Searching for new-type, eco-friendly, and Earth-abundant thermoelectric materials, which can be used as an alternative to the high-cost bismuth telluride, is important for near-room-temperature applications. In this work, nanostructured monoclinic Cu2 Se with a low carrier concentration has been synthesized by a wet mechanical alloying process combined with spark plasma sintering. Such a low carrier concentration, which originates from the effectively suppressed Cu deficiencies during the fabrication process, induces a relatively low electrical conductivity and carrier thermal conductivity. Besides, the nanostructured grains combined with point defects and phonon resonance enhance the phonon scattering to induce a low lattice thermal conductivity without sacrificing the electrical transport properties. As a result, our nanostructured monoclinic Cu2 Se obtains a figure of merit of 0.72 at 380 K with good thermal stability. This work indicates that nanostructured monoclinic Cu2 Se is a promising near-room-temperature thermoelectric material.